The role of cell migration and microchimerism in the induction of tolerance after solid organ transplantation. - Jindal, R. M. (BMJ Group, 1997)
A new hypothesis has been proposed which states that microchimerism is the basis for the clinical tolerance seen in long-term survivors of solid organ transplants. Efforts to enhance microchimerism include simultaneous infusion of bone marrow of donor origin and transplantation of a solid organ. Studies are in progress to verify the phenomenon of microchimerism and its role in clinical tolerance.